PERTANGGUNGJAWABAN PEMBAYARAN MANFAAT PENSIUN PT IFG LIFE TERHADAP PENSIUNAN PT POS INDONESIA - Edison Edison; Mahlil Adriaman; Benny Rusli (Ensiklopedia of Journal, 2023)
PT Asuransi Jiwasraya, which was supposed to carry out the obligation to pay pension benefits to hundreds of PT Pos Indonesia retirees, did not do well because this state-owned company was restructured. One of the restructuring programs is transferring customer data to IFG Life Insurance, one of the government's insurance companies. This can make its customers relieved because of the promising solution for paying the pension benefits. But even though PT Asuransi Jiwasraya has been restructured by IFG Life, it doesn't necessarily make customers satisfied and confident because after waiting for several months or even years there are still pensioners who have not received retirement benefits. For this reason, the authors conducted empirical research on PT Pos Indonesia to find out the extent of IFG Life's responsibility to customers, especially PTPos Indonesia retirees.